Premature rupture of membrane - Evaluation of incidence and risk factors in a tertiary Medical College Hospital - Ummul Nusrat Zahan; Nigger, Most Nasrin; Sheuly Akter (Bangladesh Critical Care Journal, 2023)
Background: Premature rupture of membrane (PROM) is defined as rupture of membrane before onset of true labour pain and one of the most common complications of pregnancy. It is associated with maternal morbidity and perinatal morbidity and mortality. Objective of this study is to determine the incidence and risk factors of pregnant woman with PROM admitted in a tertiary medical college in Bangladesh. Materials and methods: This prospective observational study was conducted in the Department of Obstetrics and Gynaecology at Khawaja Younus Ali medical college, Sirajgonj from 1st January 2021 to 31st December 2021. In this period total admitted antenatal patients were 8117. Among the pregnant patients with PROM were 665 and their weeks of gestation were > 28 weeks. Data was collected by an interviewer with semi structured questionnaire & check list. Results: Incidence of PROM was 9.3%. PROM was found to be frequent (39.1%) in younger age group between 21-25 years. Majority of the patients were housewife (71%). Maximum (61%) patient’s education level was up to secondary. PROM is extremely influenced by low socioeconomic status which was (49.1%) of cases in our study. It was also common in multigravida (67.2%) and term PROM was higher (56.4%) than preterm PROM (43.6%). Analysis of risk factors revealed etiology was unknown in 53 (48%) cases, anemia (16 %), lower genital tract infection (7.2%), UTI (19%), previous history of PROM (26.3%), malpresentation (15%) multiple pregnancy (6.7%) DM and GDM (10.5%) were commonly associated with PROM. Conclusions: Early identification of various risk factors causing PROM and their management can prevent premature deliveries and its complications to some extent as well as serious maternal complication like Chorioamnionitis. Bangladesh Crit Care J September 2023; 11 (2): 109-112